Knowledge/recognition: counting and the predicament of the permeable biopolitical state - Johansen, Nicolay B. (Theoretical criminology, 2020)
This article draws a model for viewing border politics based on experiences in Norway. The starting point is that the authorities do not count irregular resident migrants and openly refuse to help this group. While this makes governing this group harder, this choice makes sense from the point of view of the problem of sovereignty. Border policies in general and the decision not to count is a solution to ‘the predicament of permeable nation states in an age of migration’. What is not openly admitted is a tolerance for administrative efforts that both channel assistance to irregular migrants and keep track of their numbers. There is a general denial of the predicament, but also a strong tendency to ‘adapt’. The article examines the situation in Norway, but there are reasons to believe that the predicament defines politics in the EU and elsewhere.